Análisis de la variación hereditaria de líneas F2 de arroz (Oryza sativa L. ssp. indica) resultantes de cruzamientos con un progenitor femenino portador del gen CLEARFIELD - Santelices Villalta, Jean Carlos (2020)
This experiment was carried out from the planting of rice F2 lines (Oryza sativa L. ssp. indica) resulting from crossings with a female parent carrying the CREALFIELD gene, which confers resistance to the herbicide imazetapir. This study was carried out at the Experimental Farm "San Pablo", of the Faculty of Agricultural Sciences of the Technical University of Babahoyo-Ecuador. The objectives were the following: a) To evaluate the effect of the herbicide imazetapir on F2 rice plantlets, segregating from a female parental line carrying the CLEARFIELD gene; b) To determine the hereditary variability of the segregating populations under study and; c) To select F2 segregating rice tolerant and / or resistance to the imazetapir herbicide. Randomized Complete Design with 24 treatments, 11 progenies and 12 parental lines were used. An analysis of variance, graphics were used to identify the individuals of interest, and their averages were analyzed using the Tukey test at 5% probability. This study concludes that, with respect to the chlorophyll content, there is a difference between the progenies and parental lines evaluated before and after the herbicide application. Regarding the degree of toxicity produced by the herbicide imazetapir, it turned out that the Br-101-UTB genotype, which is the parental with Imazetapir resistance, was minimum affected, obtaining a value of 1.15%. In the case of progenies where the parental line was Br-101-UTB acted as feminine parental line, low grades were also obtained that were from 2.34 to 19.25% (ALAM scale), and from 66.67 to 97 % in the parental lines, resulting with the highest range of damage by the herbicide. The averages of the variable degree of toxicity, according to the analysis of variance, were highly significant among the genotypes studied, with a CV. of 26.45%. The results express that the gene of resistance to imazetapir, is a gene of easy introgression in the progeny, when a parent with resistance to imazetapir, acts as a female parent, response that was observed in the progenies F2 with high resistance to imazetapir herbicide, unlike of the parents treated with the same dose, where all of them were highly affected by the herbicide, except the female parent Br-101-UTB.